Performance of FRP-encased Steel-Concrete Composite Columns - Karimi, Kian (My University, 2011)
The thesis summarizes the experimental and analytical results of studies on the behavior of two FRP-encased steel-concrete composite columns under axial loading. Composite columns have been conventionally constructed using steel and concrete. This study utilizes FRP in combination with steel and concrete to manufacture composite columns with enhanced behavior. The first type of column is a concrete-encased steel column wrapped with epoxy-saturated glass and carbon fiber reinforced polymer (GFRP and CFRP) sheets in the transverse direction. The second type of composite column utilizes a GFRP tube that surrounds a steel I section column, which is subsequently filled with concrete.
To the best of the author's knowledge, columns comprising FRP, steel and concrete in the shape of the proposed composite systems has not been reported on in the literature. This study includes two major phases. In the first phase, behavior of stub columns is investigated where stability effects are ignored and failure is governed by the loss of cross-sectional strength. In the second phase, influence of stability on the behavior of the proposed composite columns is studied by testing specimens with various slenderness ratios.
To investigate the cross-sectional strength, a total of nine short (500 mm in height) composite column specimens were constructed and tested under axial compression. Five specimens were wrapped with FRP sheets and the remaining four were constructed using a GFRP tube. Experimental results showed significant enhancement in the behavior of the composite columns which was achieved due to confinement and composite action between the constituent materials. The compressive strength of the confined concrete core in the composite specimens constructed using FRP sheets and GFRP tube increased by a factor of 2.4 and 1.8, respectively. An analytical model was developed to predict crosssectional behavior of the proposed composited column.
With the primary objective of investigating the influence of slenderness on the behavior of the composite columns, ten additional column specimens, ranging between 1,000 mm and 3,000 mm in height, were tested. Five specimens were constructed using FRP sheets and five constructed using the GFRP tube technique. It was found that the compressive strength of the confined concrete core in the longest tubular composite specimen was reduced to approximately 60% of that of the corresponding short specimen. No confinement was achieved in the longest FRP wrapped composite column specimen.
Three bare steel columns, ranging between 500 mm and 3,000 mm in height, were also tested to facilitate comparison with the composite columns in terms of increased axial capacity, as well as stiffness and energy dissipation characteristics of the columns. The compressive strength, elastic axial stiffness and ultimate axial strain of the bare steel columns increased by a factor of up to 10, 6 and 3, respectively, in the composite columns constructed utilizing the concrete-filled GFRP tube. These factors were reduced to 5 .2, 2.5 and 2.6, respectively, in the concrete-encased steel columns wrapped with FRP jackets.
Finally, an analytical model was developed to establish the capacity curves for the proposed composite columns accounting for slenderness effects. A simple design equation to predict the compressive strength of the tubular composite columns was proposed based on the capacity curve generated from the analytical model. Compressive capacity of the composite columns predicted using the proposed design equation showed favorable agreement with the experimental results.
Keywords: FRP; Steel-concrete; composite column; axial loading